Interaction of SARS-CoV-2 and SARS-CoV-2 vaccines with renin angiotensin aldosterone system, clinical outcomes, and angiotensin (1-7) as a physiological treatment recommendation: hypothesis and theory article - Ali Rıza Aktaş (Frontiers in Medicine, 2025)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has affected all of humanity since the first case was reported and spread rapidly around the world, creating a pandemic. Despite the repurposing of many drugs and the development of vaccines, effective treatment and protection are limited. In addition, SARS-CoV-2 continues to be a current public health problem with complications, identifying cases of long-term Covid syndrome, and detection of vaccine-related adverse events. It can be said that the most important factor underlying all these problems is that the interaction between SARS-CoV-2 and renin-angiotensin-aldosterone system (RAAS) is not completely understood despite extensive research. Although different disciplines have limited determinations from their own perspectives regarding the communication with RAAS, it has not been sufficiently expressed in a way to see the whole picture. In this study, it is tried to see the whole picture in the interaction of RAAS and SARS-CoV-2. It is detected inadequacies in treatments and interactions that may be design errors in vaccines. These determinations also show that our templates for producing treatments are not sufficient. For this reason, we have to develop our templates with what we have learned specifically about SARS-CoV-2. Considering the accuracy of our hypothesis on the SARS-CoV-2 - RAAS relationship, Ang(1-7) can be considered a strong option for treatment. Although the SARS-CoV-2 pandemic seems to be over, epidemics and even new pandemics are likely to occur with new mutations.